Multiple rapid-responsive probes for hypochlorite detection based on dioxetane luminophore derivatives - Yingai Sun; Yuqi Gao; Chunchao Tang; Gaopan Dong; Pei Zhao; Dunquan Peng; Tiantian Wang; Lupei Du; Minyong Li (Elsevier, 2022)
In recent years, various methods for detecting exogenous and endogenous hypochlorite have been studied, considering its essential role as a biomolecule. However, the existing technologies still pose obstacles such as their invasiveness, high costs, and complicated operation. In the current study, we developed a glow-type chemiluminescent probe, hypochlorite chemiluminescence probe (HCCL)-1, based on the scaffold of Schaap's 1,2-dioxetane luminophores. To better explore the physiological and pathological functions of hypochlorite, we modified the luminophore scaffold of HCCL-1 to develop several probes, including HCCL-2, HCCL-3, and HCCL-4, which amplify the response signal of hypochlorite. By comparing the luminescent intensities of the four probes using the IVIS® system, we determined that HCCL-2 with a limit of detection of 0.166 μM has enhanced sensitivity and selectivity for tracking hypochlorite both in vitro and in vivo.